The effects of immersive simulation on targeted collaboration skills among undergraduates in special education - Robbins, Sandra H.; Gilbert, Kristen A.; Chumney, Frances L.; Green, Katherine B. (Teaching and Learning Inquiry, 2019)
The use of immersive simulation as a pedagogical tool has great potential for making a significant impact on student learning in higher education. In this study, the effect of immersive simulation was evaluated for a cohort of undergraduate special education majors. The investigation aimed to determine whether facilitating an immersive co-planning simulation would have an impact on targeted collaboration skills and whether vicarious observational learning would occur for students who observed the simulation. Pre-service teachers in special education were evaluated by their peers on their ability to demonstrate knowledge of (1) co-teaching and co-planning, (2) professional communication, and (3) supports for students with disabilities. The results indicate that they did a better job of facilitating a co-planning session after having first practiced doing so via immersive simulation during a previous class session. It was also discovered that vicarious observational learning during immersive simulation positively affected performance.